Examining Student’s Motivation in Using Google Classroom Out of Class Language Learning Activities - Asmawati Asma; Nur Rizky Alfiani Syuaib; Syenja Aradhanawaty (LP3M UMKendari, 2022)
This study aims to determine the motivation of students to use google classroom in the process of learning English. This research was conducted at SMP Negeri 1 Sampara, Konawe Regency. To answer the research questions, questionnaires were administered to 27 research subjects and interviews were conducted with 6 students. This research design uses qualitative methods with data collection using questionnaires and interviews. The findings are categorized into 4 aspects: 1) desire and interest in learning; 2) encouragement in the learning process; 3) self-respect and respect during learning activities; 4) achievement in learning. The results show that the development of technology-based learning media such as the google classroom application has its own challenges for teachers, in managing applications, design and learning strategies. The use of google classroom as a learning medium has a positive effect on increasing student motivation. In this context, the teaching and learning process can generate desire, interest, motivation and teaching and learning, besides that Google Classroom can also help students to facilitate understanding of the subject matter.